Melatonin combined with sorafenib synergistically inhibit the invasive ability through targeting metastasis-associated protein 2 expression in human renal cancer cells - Chu-Che Lee; Po-Yu Huang; Yi-Hsien Hsieh; Yong-Syuan Chen; Jen-Pi Tsai (Tzu Chi Medical Journal)
Objectives: Renal cell carcinoma (RCC) was the most common and lethal urological malignancy with the dismal outcome when distant metastasis. Melatonin was known as a potential oncostatic agent against several types of malignancy and sorafenib had been considered as an agent to treat RCC, but the synergistic effects of melatonin and sorafenib on human RCC have not been elucidated. Materials and Methods: Human renal cancer cell lines (Caki-1 and ACHN) were treated with melatonin combined with sorafenib were detected the cell growth and cell cycle by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-tetrazolium bromide assay and flow cytometry. The ability of cell migration/invasion was performed with in vitro migration and invasion assay. The proteins and mRNA expression of metastasis-associated protein 2 (MTA2) from the RCC cells were measured by quantitative reverse transcription-polymerase chain reaction and western blotting. Clinical significance of MTA2 in RCC tissues was analyzed from The Cancer Genome Atlas database by using TISIDB software. Results: Our results showed that melatonin combined with sorafenib, sorafenib or melatonin-treated alone did not induce the cytotoxic effects or cell cycle arrest in human RCC cells and HK2 cells. Additionally, cotreatment with melatonin and sorafenib synergistically reduced migration and invasion in human Caki-1 and ACHN cells through synergistically suppression of MTA2 expression. Bioinformatics analysis showed that MTA2 expression significantly correlated with overall survival (P < 0.002), tumor grade (P < 0.001) and tumor stage (P < 0.001) in human RCC. Conclusion: Our results demonstrated that concomitantly used melatonin and sorafenib could significantly reduce the abilities of migration and invasion of RCC cells through inhibiting MTA2. We considered that this novel promising combination strategy towards the treatment of RCC, but further studies are warranted.